A Single Center Experience With Long-Term Ustekinumab Use and Reinduction in Patients With Refractory Crohn Disease. Issue 1 (27th February 2020) - Bennett, Audrey; Evers Carlini, Lauren; Duley, Caroline; Garrett, Ailish; Annis, Kim; Wagnon, Julianne; Dalal, Robin; Scoville, Elizabeth; Beaulieu, Dawn; Schwartz, David; Horst, Sara
Abstract: Background: Ustekinumab was approved for moderate and severe Crohn's disease (CD) in 2016, but little is known about long-term outcomes. Methods: A retrospective study evaluated all patients with CD treated with ustekinumab, including patients with reinduction. C-reactive protein (CRP), Harvey-Bradshaw Index (HBI), Short Inflammatory Bowel Disease (SIBDQ), and endoscopy outcomes were collected prospectively. Results: Ninety-six patients received ustekinumab, resulting in improvement in CRP, HBI, and SIBDQ scores with 68% endoscopic improvement/remission. Thirty-four patients underwent reinduction, resulting in improved HBI and CRP. Conclusions: Ustekinumab in refractory CD results in significant clinical and endoscopic improvement and reinduction may be a viable option to recapture response. Lay Summary: This study shows that ustekinumab can be used to improve symptoms and disease markers in patients with severe Crohn disease who have failed prior medications. The study also demonstrates that reinduction can help regain response if needed.